ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN-PERUSAHAAN MANUFAKTUR DI BURSA EFEK IINDONESIA TAHUN 2009-2011 - Moningka, Petrus (JBE (Journal of Business and Economics); Volume 12 No.1, 2013 JBE UNKLAB, 2013)
The objective of his research are to test the influence of Dividend Distributon, Debt Policy, Investment Decision, Institutional Ownership, and ROA both individually and simultaneously to firm’s value. The fir’s value as atied variable in this research uses PBV (Price to Book Value). Statistic analysis used in this research uses the simple linear regression to know independent variable individually toward dependen variable, and uses multiple linear regression to know all independent variable’s influence upon dependen variable. As a sample, this research uses manufacturing companies by using purposive sampling method during 2009-2011. The number of companies that required the given criteria are 37 companies. As the result of this reseach , it is found that dividend payment, debt  policy, and investment policy, do not influence the firm’s value statistically. On the other hand, for the variables of institutional ownership and ROA, they influence the firm’s value significantly. It is found that in simultaneously test the variables of dividend distribution, debt policy, investment policy, institutional ownership and ROA have significant influence toward firm’s value.